Survival Analysis of the Risk Factors Affecting the Survival Time of Diabetic Patients - Nithya Jayaseeli; Kannadasan Karupaiah; Idhris, Mohamed; Ajayan Kamalasanan; Prabu Neethidoss; Sivasankar Prabaharan; Palanivel R.M; Vinoth Raman (Unnes Journal of Public Health, 2025)
This study aimed to analyze the risk factors that affect the survival time of diabetic patients. It used the diabetes health indicators dataset (2015) collected from the American population by the “Centers for Disease Control and Prevention,” United States, through the “Behavioral Risk Factor Surveillance System” in 2015. The dataset comprised 70,692 responses, among which every 320th sample was selected to get the estimated sample size of 221 using the systematic sampling method. The collected data was analyzed through a statistical package for the social sciences (SPSS) software 27.0. The outcomes found that risk factors such as age, high cholesterol, smoking, heavy alcohol consumption, physical activity, high blood pressure, heart disease or attack, general health, serious difficulty in walking or climbing stairs, and stroke were significantly associated with the risk of diabetes. General health was a significant predictor of the risk of diabetes. The estimated survival probability of diabetic patients decreases as their age progresses due to risk factors such as smoking, heavy alcohol consumption, stroke, high blood pressure, and heart disease or attack. Also, it decreases with their age if those patients are physically inactive. These findings highlight that more active strategies are required to comprehensively control risk factors to reduce the burden of diabetes among the general inhabitants.